PENGARUH METODE MULTISENSORI TERHADAP KEMAMPUAN MENULIS PERMULAAN PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS II SDN 248 GARECCING KECAMATAN TONRA KABUPATEN BONE - Magfirah, Nur Sakinah (MACCA : Science-Edu Journal, 2025)
The research is a quantitative research wtih a pre-experimental design type one group pre-test-post-test which aims to determine the significant influence of the use of multisensory method initial writing skills in Indonesian languange lessons of class II students at SDN 248 Gareccing, Tonra District, Bone Regency. The variables in this research are the multisensory method (independent variable) and beginning writing skills (dependent variable). The population of this research was all class II students at SDN 248 Gareccing, totaling 23 students. The sampling technique used is a saturated sampling technique because all members of the population are used as samples. Data collection techniques use tests. The data analysis technique uses descriptive statistics and inferential statistics. The results of the research were that before the multisensory method learning treatment was given, the test result obtained by students tended to be low with an average (mean) of 30,22 in the very poor category and after giving the multisensory method the student test results increased with an average (mean) 75,48 is in the good category. The conclusion of this research is that there is a significant influence on initial writing ability in Indonesian languange lessns after multisensory method foe class II students at SDN 248 Gareccing, Tonra District, Bone Regency.